PENGARUH KUALITAS ADMINISTRASI TATA USAHA TERHADAP LAYANAN PENDIDIKAN DI MAN 2 MODEL MEDAN - Rheina Sayla; Dinda Putri; M. Yasir Ardiansyah; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2026)
The quality of administrative services plays an important role in supporting the effectiveness of educational services in formal educational institutions. Well-organized administration contributes to the smooth learning process, user satisfaction, and overall institutional quality improvement. This study aims to analyze the effect of administrative service quality on educational services at Madrasah Aliyah Negeri (MAN) 2 Model Medan. A quantitative approach with a correlational method was employed involving 21 respondents consisting of teachers and educational staff. Data were collected using a five-point Likert scale questionnaire and analyzed through validity, reliability, normality, homogeneity, and t-tests using SPSS. The results indicate that the research instruments were valid and reliable, the data were normally distributed and homogeneous, and there was a significant effect of administrative service quality on educational services, with a significance value of 0.000 (<0.05). These findings confirm that improving administrative service quality directly contributes to enhancing educational service quality.